Theoretical study on the atmospheric degradation mechanism and subsequent products of E, E‐2, 4‐hexadienal with hydroxyl radical. Issue 7 (6th December 2020) - Sun, Yanan; Yao, Junfang; Tang, Yizhen; Zhang, Yunju; Wu, Wenzhong; Sun, Jingyu
Abstract: E, E‐2, 4‐hexadienal is probably a precursor of secondary organic aerosol (SOA) and plays an important role in the atmospheric chemistry. Its main degradation routs are the reactions with OH, Cl, NO3 as well as photolysis. Atmospheric hydroxyl radical, as the most important oxidant, generally controls the removal of volatile organic compounds in the atmosphere. Thus, the quantum chemical calculations are used to investigate the reaction mechanism of E, E‐2, 4‐hexadienal with hydroxyl radical, which would give us a better understanding for the main degradation products. The reaction paths of E, E‐2, 4‐hexadienal with OH radical have been calculated accurately by using the BMC‐CCSD//M06‐2X/6‐311G (d, p) level at atmospheric pressure and room temperature. There are six hydrogen abstraction and four carbon addition paths at the first stages of this reaction. Due to the low energy barrier and exothermic reaction, the ten paths would contribute to the total reaction. Furthermore, the peroxy (RO2 ) and alkoxy (RO) radicals from the most important adduct IM1(CH3 CHOHCHCHCHCHO) would be formed in the atmospheric environment. Hence, the reaction mechanism of the peroxy radical (CH3 CHOHCHO2 CHCHCHO) with NO, NO2, HO2, and self‐reaction have been also studied by using the same quantum chemical methods. And the reaction paths of alkoxy radical (CH3 CHOHCHOCHCHCHO) have been also originally studied. It is found that the subsequent reactions play a key role in the cycling of atmospheric radicals, production of ozone, and SOA formation. What is more, the reaction mechanism of this study accords with the reported experimental observations. Meanwhile, the theoretical rate constant of 1.05 × 10 −10 cm 3 molecule −1 s −1 of E, E‐2, 4‐hexadienal with OH reaction at 298 K is close to experimental data. The atmospheric lifetime of E, E‐2, 4‐hexadienal with OH radical is about 2.6 h at 298 K. This study provides insight into the transformation of E, E‐2, 4‐hexadienal in the atmospheric environment. Abstract : The first stages of E, E‐2, 4‐hexadienal initiated by hydroxyl radical have been studied by quantum chemical calculations. And the degradation paths of peroxy radical RO2 (CH3 CHOHCHO2 CHCHCHO) and alkoxy radical RO (CH3 CHOHCHOCHCHCHO) with NO, NO2, HO2, and self‐reaction were also firstly studied.